Analisis Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja: Studi Kasus pada Karyawan di Pujasera Palangka Raya - Vivy Kristinae (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2018)
Palangka raya as the one largest city at central Borneo in Indonesia, become more popular for its culinary industry from the smallest scale of food community until the high end scale of fine dining restaurant. The amount of the restaurant business is gradually increase, this phenomenon makes a good advantage for the local people especially the amount of job opportunity. In the other side, restaurant industries in Palangka raya also facing the high rivalry and competition among individual restaurant business. In order to survive from the competition , each business should have its own competitive advantage. Human resource is one of the most important resource to gaining the competitive advantage, since it related with human being at the final result how excellent was the planning process, human aspect will take a final decision for the result of a process. The research is focusing on the relation between motivation and job satisfaction, the writer saw the phenomenon in trend japaness food, that some employee feel satisfy with their work, although the working pressure is high. According to the pre-interview, the writer found that the employee feel comfortable with their work because of their workmates is very social and feel like a new small family in working environment. This research used quantitative approach for the data process, and simple linear regression for the analysis. The result of the research is that job satisfaction is significantly affected by motivation